Contact pressure with guaranteed tight in coupling of bushing and long shaft - I. L. Ryazantseva (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article describes an analytical method for determining the average value of contact pressure in pressure coupling taking into account the geometric features of the parts to be connected by fitting. The calculated dependencies given in the publication are obtained by the author under the condition of uniform radial displacement of the mating surface of the male part calculated using the Lamé formulas. The method is simple, clear, provides sufficient accuracy for engineering calculations. It can be used both in the design of smooth cylindrical joints with tension, and joints modified by shallow grooves